Financiamento da educação especial : um olhar para a escolarização dos/as estudantes surdos/as e com deficiência auditiva - Leite, Charles de Castro (2024)
The right to education is ensured for students eligible for special education services, preferably in regular classes within the mainstream school system. However, to make this a reality, it is necessary to consider education funding policies. In this context, the schooling of deaf and hard of hearing students must be considered, which, in the advocacy efforts of the disability rights movement, is based on guaranteeing the right to education in Brazilian Sign Language (Libras). Given this scenario, our general objective is to investigate the funding of special education in the Municipal School System of Cachoeiro de Itapemirim-ES, in relation to the schooling process of deaf and hard of hearing students, from 2018 to 2022. As a theoretical foundation, we adopt the contributions of authors such as Araújo, Cury, Jannuzzi, Mazzotta, Kassar, Damázio, Dorziat, Damázio and Alvez, Oliveira, Salvador, Melchior, França, and Prieto. This research is qualitative in nature (Lüdke; André, 2017), of a documentary type, with content analysis. As a result of our study, we identified that special education was included in the municipality's budget planning from 2018 to 2022. Regarding the funds allocated to education, we observed the financial dependence of the municipality on resources from federal entities, with 71% of the funds coming from constitutional transfers and only 29% from municipal revenues. This highlights the importance of these transfers for the composition of municipal revenue and ensuring the provision of basic education. We raise concerns about the absence of special education in the Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação revenue statement, which constitutes a weakness in the transparency of resources for the maintenance and development of special education. In the analysis of expenses related to education, we infer that the "Education" function had the highest liquidated expense (29%) when compared to other functions. Regarding the subfunctions of the "Education" function, we infer that the subfunction with the highest expenditure of funds was "Early Childhood Education" (54%), followed by "Primary Education" (44%), and subsequently "Special Education" (2%). Concerning the "Special Education" subfunction, we observed variations in the records of information about the expense elements listed in MDE, which did not allow us to fully understand the actual amount of resources allocated to special education. Regarding the resources allocated to the schooling process of deaf and/or hard of hearing students, we did not find specific details in the analyzed documents. However, these students are eligible for special education and are therefore included in the special education funding of the municipality of Cachoeiro de Itapemirim-ES. To initiate the discussion on the per-student/per-year cost related to specialized educational services for deaf and hard of hearing students, an estimate of the actual per-student cost was made, focusing on the remuneration of professionals working in this service. The estimated actual per-student/per-year cost was R$ 24,816.99 for the PEB-B-D.A. teacher (25h) and R$ 1,266.71 for the PEB-B-SRM teacher (25h), equivalent to R$ 2,068.08 and R$ 105.56 per month, respectively. These figures indicate a high actual per-student/per-year cost for deaf and hard of hearing students in the municipality, considering the organization and performance of the PEB-B-D.A. teacher per student and school. Thus, we observed that the municipality allocated funds for special education funding during the period from 2018 to 2022, which includes resources for ensuring the schooling process of deaf and hard of hearing students. However, the study points to the need to ensure transparency in financial data for effective planning, execution, and monitoring of public resources, as well as reflection on the organization of specialized educational services for deaf and hard of hearing students. This includes considering the importance of the meeting of deaf peers for the formation of deaf identity, as well as the need for specific training for professionals working in specialized educational services in multifunctional resource rooms. Lastly, we emphasize that ensuring the right to education requires public policies and funding to guarantee a quality standard for all students